Henry James and the language of experience - Meissner, Collin (Cambridge University Press, 1999)
"In Henry James and the Language of Experience, Collin Meissner examines the political dimension to the representation of experience as it unfolds throughout James's work. Meissner argues that, for James, experience was a private and public event, a dialectical process that registered and expressed his consciousness of the external world."--Jacket